Lancar iqra' dari dasar sampai mahir / Ahmad Saiffuddin ; penyunting, Ahmad Saiffuddin; ilustrator, Mbah Wid - AHMAD SAIFUDDIN, 1983-; Ahmad Saiffuddin; Mbah Wid (Laksana Kids, 2016)
123 hlm. : ilus. ; 26 cm